The climatic, biological, and strategic effects of nuclear war : hearing before the Subcommittee on Natural Resources, Agriculture Research, and Environment of the Committee on Science and Technology, House of Representatives, Ninety-eighth Congress, second session, September 12, 1984 (U. S. Government Printing Office, 1985)
Includes bibliographical references. Donation of Edward Corcoran.